Non-compaction of left ventricular myocardium in sub-Saharan African adults. Issue 2 (8th June 2017) - Gaye, Ngoné Diaba; Ngaïdé, Aliou Alassane; Bah, Mamadou Bassirou; Babaka, Kana; Mbaye, Alassane; Abdoul, Kane
Abstract : Background: Non-compaction of the left ventricle (NCLV) is an unclassified cardiomyopathy due to intrauterine arrest of compaction of the loose interwoven meshwork. Only a few studies involving sub-Saharan Africans insmall numbers have been published. The aim of our study was to determine the diagnostic, therapeutic and prognostic aspects as well as the clinical course of NCLV in a black African population. Methodology: A multicentre retrospective study was carried out between November 2007 and June 2012 in two cardiology departments in Dakar. Patients who met the echocardiographic criteria for NCLV were included in the study. Results: 35patients with the diagnosis of NCLV were evaluated in the study. Their mean age was 47±18.4 years. Heart failure was found in 77.1% of the patients. The most frequent electrocardiographic abnormalities were left ventricular hypertrophy (LVH) (46%) and sinus tachycardia (43%). Mean non-compaction/compaction ratio was 2.84±0.68 with preferential localization in the apex of the left ventricle. The main complications observed were cardiogenic shock (23.5%), pulmonary embolism (6.3%) and ventricular tachycardia (5.9%). Diuretics and ACE inhibitors were the medications most often prescribed. Age >60 years (p=0.04), male gender (p=0.03) and the occurrence of complications during follow-up (p=0.04) were noted to be predictors of poor prognosis. Conclusion: Contrary to previous beliefs, NCLV may not be less common in black Africans than in other ethnic subgroups. Clinicians in Africa should be made aware of NCLV so that it can be diagnosed at earlier stages.